Fundos competitivos para o financiamento da pesquisa agrícola no Brasil: o caso do PRODETAB - Embrapa - Gonçalves, Ana Maria A. L. Rodrigues (2001)
Competitive Programs for agricultural research financing are widely applied in developed countries, but only after years 90, the introduction of this mechanism had been intensified in developing countries, specially in Latin America, due to the decline of investments to agricultural research through federal government resources. Consequently the research organizations started to look for alternative sources to finance their research agenda. The present study aims to analyze and to discuss this mechanism importance as a creative and innovative alternative of financing agricultural research in Brazil. The analysis is based in a literature review about the financing mechanism and the case study of PRODETAB - Competitive Grants Scheme, implemented and coordinated by Embrapa. The objective was to evaluate the importance and relevant contribution of Competitive Grants as a mechanism of great efficiency in the allocation of public research funds and to the quality improvement of research projects.